2018
DOI: 10.1007/s10103-018-2478-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of CO2 laser-assisted posterior cordectomy in bilateral vocal cord paralysis in 132 cases

Abstract: The purpose of the study was to assess the role of laser-assisted posterior cordectomy in the management of patients with bilateral vocal cord paralysis. We aimed an analysis of 132 consecutive patients treated by CO2 laser posterior cordectomy, aged 38–91, 31% tracheotomized on admission. Cordectomy was performed under microlaryngoscopy using CO2 laser (Lumenis AcuPulse 40 CO2 laser, wavelength 10.6 μm, Lumenis Ltd., Yokneam, Israel). We looked at the number of laser glottic procedures necessary to achieve de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
(42 reference statements)
2
16
3
1
Order By: Relevance
“…We showed that BVFP-related dyspnea was not significantly relieved by glottal enlargement in 5% of the patients 1 month and in 3% of the patients 3 months after surgery. The results of our registry showed that age is a significant predictor for post-treatment dyspnea, while it was not found to be reliable predictor for decannulation, which is in contradiction with the results of a previous study [10]. However, the results of our registry confirmed that older patients (≥ 65 years old) required more medical care.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We showed that BVFP-related dyspnea was not significantly relieved by glottal enlargement in 5% of the patients 1 month and in 3% of the patients 3 months after surgery. The results of our registry showed that age is a significant predictor for post-treatment dyspnea, while it was not found to be reliable predictor for decannulation, which is in contradiction with the results of a previous study [10]. However, the results of our registry confirmed that older patients (≥ 65 years old) required more medical care.…”
Section: Discussioncontrasting
confidence: 99%
“…We assume that this finding could be linked to the fact that procedures based on physiological abduction of the arytenoid cartilage seem to be the most effective [13]. In summary, while surgical glottal enlargement is likely to be more cost-effective than tracheostomy [14], it still show a relevant risk of revision in the 2 years following the first treatment, as also reported by Jackowska et al [10]. Thus, it is important to consider new, more physiological approaches with a potential low rate of revisions.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although rates of complications have been reported, there is very little in the current literature regarding how specific patient factors and perioperative management strategies may influence complication rates in patients undergoing TPC. One previous study identified GERD and diabetes mellitus (DM) as comorbidites that decreased the likelihood of decannulation in patients undergoing TPC for BVFP 13 . We found that patients with PGS had worse outcomes than those with BVFP.…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, the provision of good quality of life in those patients also includes the restoration of the remaining functions of the larynx, such as phonation and swallowing. According to Jackowska et al, the most important indices of treatment effectiveness in patients with tracheostomy are the rate and time of decannulation [91]. Therefore, it seems to be of utmost importance to avert tracheostomy by the fastest possible revision of the neck in case of iatrogenic bilateral vocal fold paralysis, and to perform end-to-end anastomosis if nerve discontinuation is confirmed.…”
Section: Discussionmentioning
confidence: 99%